The Effect Of Window Design On Daylighting And Thermal Performance Of Classrooms In Penang, Malaysia - Al-Ashwal, Najib Taher Ahmed (2020)
The quality of the indoor environment including the lighting conditions is crucial in classrooms as it directly affects students’ performance and productivity. Natural light is the best source of light from visual and aesthetic perspectives and energy efficiency views. The luminous efficacy of daylight in Malaysia is excellent and could meet most of the required luminance during the day. However, in Malaysian schools, it was found that all the lights are switched on throughout the day and only be off during break time and at the end of the day. Besides, most of the classrooms in Malaysia, in schools or higher institutions, daylighting is not efficiently utilised. This study investigates the impact of window design elements on the daylighting performance and thermal load in classrooms in national high schools in Penang, Malaysia. The study is divided into two phases. First, the fieldwork phase, which aims at evaluating daylighting performance in high schools’ classrooms in Penang through measuring incident illumination levels inside the examined classrooms. The results revealed that more than enough daylight is provided in most classrooms because of the relatively large classrooms’ windows with clear glass. The average illuminance found from these measurements is between 400 lux more than 1000 lux which is higher than by the standards recommended value. The average daylight factor recorded in the classrooms is between 6.4 and 9.2% in most of the times. These values are relatively high and may result in glare problems. The second phase includes the modelling and simulation using Design-Builder for a typical classroom in the high schools in Penang.